Genetic Basis of Congenital Upper Limb Anomalies: Analysis of 487 Cases of a Specialized Clinic. Issue 12 (December 2013) - Carli, Diana; Fairplay, Tracy; Ferrari, Paola; Sartini, Silvana; Lando, Mario; Garagnani, Lorenzo; Di Gennaro, Giovanni Luigi; Di Pancrazio, Luciana; Bianconi, Giorgia; Elmakky, Amira; Bernasconi, Sergio; Landi, Antonio; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Specific data regarding the frequencies of the congenital upper limb anomalies (CULA) according to their etiology are hardly available due to the heterogeneity across classification systems. In this study, we aim at defining the CULA etiology of patients that have been evaluated at the Modena University Hospital's Congenital Hand Malformations multidisciplinary clinic in the years 2004 to 2012. METHODS Medical records of 487 patients were retrospectively reviewed. On the basis of clinical, anamnestic, and genetic data, the CULA were distributed into two main groups: (1) non‐Mendelian etiology, including prenatal exposure, somatic mutations and amniotic bands; and (2) Mendelian etiology, including single gene and genomic/chromosomal diseases. CULA were further grouped according to the embryological damage (formation, separation and growth defects) and to the involved axis (radial, ulnar, central). RESULTS A Mendelian etiology was diagnosed in 199 patients (40.9%), whereas the remaining 288 cases (59.1%) were described as non‐Mendelian. The involvement of the lower limbs, the presence of malformations in other organs and facial dysmorphisms were significantly more represented in the Mendelian cases. The formation defects were significantly more frequent in the non‐Mendelian group (p < 0.001), whereas the frequency of separation defects was higher in the Mendelian cases (p = 0.0025). Patients with non‐Mendelian etiologies showed a significantly higher frequency of central defects (p = 0.0031). CONCLUSION The two etiologies differ in terms of patient's clinical features, morphology defect and axis involvement. This data may be helpful to the clinician during the patient's diagnostic workup by indicating the necessity for genetic testing and for determining the anomaly's recurrence risk. Birth Defects Research (Part A) 97:798–805, 2013. © 2013 Wiley Periodicals, Inc.